Study on the relationship between traditional medicine syndromes in patients with peptic ulcer disease and peptic ulcer disease complicated by gastrointestinal hemorrhage - Le, Quoc Anh; Nguyen, Ngoc Le (Tạp chí Y Dược Huế, 2025)
Background: Peptic ulcer disease is quite common in the community, prone to recurrence, and associated with many dangerous complications, including gastrointestinal bleeding. According to traditional medicine, described in peptic ulcer disease belong to the category of “gastric upset”. To assist physicians in diagnosing and effectively treating this disease, while also reducing the risk of gastrointestinal bleeding, we conducted this study. Objectives: To investigate certain characteristics of traditional medicine syndromes and patterns in patients with peptic ulcer disease and those with peptic ulcers complicated by gastrointestinal bleeding. Additionally, to explore the relationship between traditional medicine syndromes and certain factors in patients with peptic ulcers and those with peptic ulcers complicated by gastrointestinal bleeding at Hue University of Medicine and Pharmacy Hospital. Materials and method: A cross-sectional descriptive study was conducted on 105 patients diagnosed with peptic ulcer disease at the General Internal Medicine - Endocrinology - Musculoskeletal Department and the Gastroenterology - Endoscopy Center at Hue University of Medicine and Pharmacy Hospital. Results: The average age was 58.05 ± 15.62 years old, with the highest percentage of patients being over 60 years old. Patients with duodenal ulcers accounted for the highest proportion in both patient groups with rates of 52.7% and 52.0%. Clinical characteristics according to traditional medicine: Excess 79.1%, Deficiency 20.9%; Qi stagnation syndrome accounted for 31.4%, Fire stagnation 27.6%, Blood stasis 22.9%, and Spleen stomach deficiency cold 18.1%. Patients with Qi stagnation, Fire stagnation, and Blood stasis had a disease duration of less than 6 months, while those with Spleen stomach deficiency cold had a disease duration of more than 12 months, which was higher than other syndromes (p<0.05). Conclusions: Duodenal ulcers were the most commonly encountered. Most patients with blood stasis syndrome were classified as Forrest IIa or IIb; there is a relationship between the characteristics of traditional medicine syndromes in the group of patients with peptic ulcer disease complicated by gastrointestinal bleeding and the Forrest classification (p<0.05).